Upaya Meningkatkan Prestasi Belajar Bahasa Indonesia Melalui Penggunaan Model Pembelajaran Complete Sentence Dengan Metode Daring Siswa Kelas IV SD Negeri 3 Kerta - Ni Made Mirnawati (Jayapangus Press, 2021)
This research was conducted at SD Negeri 3 Kerta in grade IV where the ability of students in Indonesian subjects is still low. The purpose of writing this classroom action research is to find out whether the Complete Sentence Learning Model can improve student achievement. The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study are the Complete Sentence Learning Model can improve student achievement. This is evident from the results obtained initially at 65.75, in the first cycle it became 69.75 and in the second cycle it became 78.25. The conclusion obtained from this study is that the Complete Sentence Learning Model can improve the learning achievement of fourth grade Indonesian students at SD Negeri 3 Kerta.